2017
DOI: 10.1177/0972262916681255
|View full text |Cite
|
Sign up to set email alerts
|

Pecking Order among Select Industries from India and China

Abstract: The present article tests the pecking order of various industries from India and China. Firms in each industry have been segregated into deficit and surplus groups. The empirical findings indicate that a large number of industries from India and China adhere perfectly to the pecking order during deficiency. Borrowings through long-term debt are more among Indian deficit industries, whereas Chinese industries borrow more short-term debt. The debt issues are considerably large among Indian construction, metal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Further, it has been established by means of data analysis that the more is the severity of financial constraints experienced, the lesser shall be the possibilities for firms to grow. The findings of the present study, hence, line up with work of Donaldson (1961), Jenson and Meckling (1976), Myers (1984), Tucker and Lean (2003), Johnsen and McMahon (2005), Bandari and Bajpai (2005), Bhama et al (2017), and Rajamani and Nirmal Raj (2019), who suggested and predicted slower growth rate for the financially constrained firms.…”
Section: Financial Constraints Vs Firm Growthsupporting
confidence: 91%
See 1 more Smart Citation
“…Further, it has been established by means of data analysis that the more is the severity of financial constraints experienced, the lesser shall be the possibilities for firms to grow. The findings of the present study, hence, line up with work of Donaldson (1961), Jenson and Meckling (1976), Myers (1984), Tucker and Lean (2003), Johnsen and McMahon (2005), Bandari and Bajpai (2005), Bhama et al (2017), and Rajamani and Nirmal Raj (2019), who suggested and predicted slower growth rate for the financially constrained firms.…”
Section: Financial Constraints Vs Firm Growthsupporting
confidence: 91%
“…Similarly, the discussion on the financial obstacles as the critical determinant of firm growth is polarised by Donaldson (1961), Jenson and Meckling (1976), Myers (1984), Tucker and Lean (2003), Johnsen and McMahon (2005), Gebru ( 2009), Bhama et al (2017). The above discussion therefore enables us to propose the following hypotheses:…”
Section: Wjemsd 173mentioning
confidence: 93%
“…Hence, the outcome of our study suggests that a combination of the pecking order theory and the trade-off theory rationalize the capital structure choice in the Indian context. Indian-based studies like Chakraborty (2010) and Chadha and Sharma (2015) ascertained the same, while Bhama et al (2017) backed the pecking order theory and Bajaj et al (2018) supported trade-off theory.…”
Section: Discussionmentioning
confidence: 75%
“…Other recent studies offered more favorable results for this theory. Bhama, Jain, and Yadav (2017) analyzed 405 Indian firms and 312 Chinese firms between 2003 and 2014 and obtained favorable results for the pecking order theory. However, the authors warned that the validity of this approach depends on the size of the deficit (surplus) and the industry.…”
Section: The Trade-off and Pecking Order Theoriesmentioning
confidence: 99%